Myths and the American Nation: Jefferson`s Declaration and the development of American nationalism - Smith, Brian G. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The USA as a multinational country of immigrants is nevertheless a fertile ground for competing nationalist ideologies and the consequently competing myth-building that surrounds the construction of national identity. The myth of the 1776 Declaration of Independence as an important founding document for domestic politics in the United States continues to spread through popular culture and academic textbooks. The claim of the Jefferson`s Declaration as an aspirational founding document helped establish a myth supporting creedal nationalism, but obscures the arc of the ideological debate over national identity.
Keywords: American nationalism; myth; Jefferson, Thomas (prezydent Stanów Zjednoczonych; 1743-1826); Declaration of Independence; creedal nationalism